Targeting Autophagy in Cancer: Update on Clinical Trials and Novel Inhibitors - Chude, Cynthia I. (Int J Mol Sci, 2017)
Eukaryotes use autophagy as a mechanism for maintaining cellular homeostasis by degrading and recycling organelles and proteins. This process assists in the proliferation and survival of advanced cancers. There is mounting preclinical evidence that targeting autophagy can enhance the efficacy of many cancer therapies. Hydroxychloroquine (HCQ) is the only clinically-approved autophagy inhibitor, and this systematic review focuses on HCQ use in cancer clinical trials. Preclinical trials have shown that HCQ alone and in combination therapy leads to enhancement of tumor shrinkage. This has provided the base for multiple ongoing clinical trials involving HCQ alone and in combination with other treatments. However, due to its potency, there is still a need for more potent and specific autophagy inhibitors. There are multiple autophagy inhibitors in the pre-clinical stage at various stages of development. Additional studies on the mechanism of HCQ and other autophagy inhibitors are still required to answer questions surrounding how these agents will eventually be used in the clinic.